Phosphorus-molybdenum co-doped graphite carbon nitride photocatalyst and preparation method thereof

By co-doping graphite carbon nitride photocatalysts by phosphorus and molybdenum, PMo-C3N4 with Z-type heterojunction structure was prepared, which solved the problem of insufficient photocatalytic performance of traditional graphite carbon nitride photocatalysts, and achieved efficient photocatalytic reactions and wastewater degradation.

CN119793514APending Publication Date: 2025-04-11NINGBO UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510205192.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-24
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

Traditional graphite carbon nitride photocatalysts have the disadvantages of low visible light utilization, small specific surface area, low crystallinity and fast photogenerated carrier recombination, which seriously limits its photocatalytic performance.

Method used

PMo-C3N4 with Z-type heterojunction structure was prepared by using phosphorus-molybdenum co-doped graphite carbon nitride photocatalysts by wet ball milling to improve the electron structure and improve the separation efficiency between photogenerated electrons and holes.

Benefits of technology

The efficiency of photocatalytic reaction is significantly improved, the stability and photocatalytic activity of the catalyst are enhanced, and the printing and dyeing wastewater and antibiotic wastewater can be excellently degraded.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119793514A_ABST
    Figure CN119793514A_ABST
Patent Text Reader

Abstract

The invention discloses a phosphorus-molybdenum co-doped graphite carbon nitride photocatalyst and a preparation method thereof, and the preparation method is characterized by comprising the following steps: firstly, respectively putting a nitrogen source compound, absolute ethyl alcohol, one of sodium dihydrogen phosphate, ammonium hexafluorophosphate or phosphonitrilic chloride trimer and ammonium heptamolybdate tetrahydrate into a stainless steel ball milling tank for mixing, and then grinding the mixture in a ball mill; drying the ground mixture to remove moisture; calcining the dried mixture, cooling to normal temperature after calcining, and grinding into powder to obtain phosphorus-doped graphite carbon nitride and molybdenum-doped graphite carbon nitride; then the phosphorus-doped graphite carbon nitride and the molybdenum-doped graphite carbon nitride are put into a stainless steel ball milling tank to be mixed, the follow-up preparation process is the same as that in the previous step, and the obtained product is phosphorus-molybdenum-doped graphite carbon nitride which is used as a photocatalyst; the preparation method has the advantages that the separation efficiency of photo-induced electrons and holes is remarkably improved, the stability and photocatalytic activity of the photocatalyst are enhanced, and the photocatalyst can be used for degrading organic pollutants and antibiotic wastewater.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of photocatalysts, and in particular to a phosphorus-molybdenum co-doped graphite carbon nitride photocatalyst and a preparation method thereof. Background Art

[0002] In recent years, with the increasing global environmental pollution problem, finding efficient and environmentally friendly solutions has become a hot topic in scientific research. Graphitic carbon nitride (g-C3N4) has a catalytic effect under visible light irradiation and can be used for organic pollutant degradation, water decomposition, carbon dioxide reduction and hydrogen production. However, traditional g-C3N4 has disadvantages such as low visible light utilization, small specific surface area, low crystallinity and fast recombination of photogenerated carriers, which seriously limit its photocatalytic performance. Summary of the invention

[0003] The technical problem to be solved by the present invention is to provide a phosphorus-molybdenum co-doped graphite carbon nitride photocatalyst and a preparation method thereof, which enables the prepared photocatalyst to have a Z-type heterojunction structure with good energy band matching, significantly improves the separation efficiency of photogenerated electrons and holes and the efficiency of photocatalytic reaction, and can degrade printing and dyeing wastewater and antibiotic wastewater with excellent degradation performance.

[0004] The technical solution adopted by the present invention to solve the above technical problems is: a phosphorus-molybdenum co-doped graphite carbon nitride photocatalyst, characterized in that its molecular formula is PMo-C3N4, and it is composed of 52% to 70% C, 25% to 40% N, 1.5% to 6% O, 0.2% to 2% P and 0.05% to 0.6% Mo element in mass percentage, and the photocatalyst has a Z-type heterojunction structure.

[0005] A method for preparing a phosphorus-molybdenum co-doped graphite carbon nitride photocatalyst comprises the following specific steps: (1) Sodium dihydrogen phosphate, ammonium hexafluorophosphate or hexachlorocyclotriphosphazene, a nitrogen source compound and anhydrous ethanol are placed in a stainless steel ball mill and mixed, wherein the mass ratio of sodium dihydrogen phosphate or ammonium hexafluorophosphate or hexachlorocyclotriphosphazene to the nitrogen source compound is 0.05-0.25:0.5-5, and the amount of anhydrous ethanol added is equal to the sum of the masses of the above two substances, and then all the substances are ground in a ball mill to obtain a mixture A; (2) Place a nitrogen source compound, ammonium heptamolybdate tetrahydrate and anhydrous ethanol in a stainless steel ball mill and mix them, wherein the mass ratio of the nitrogen source compound to ammonium heptamolybdate tetrahydrate is 0.5-5:0.005-0.1, and the amount of anhydrous ethanol added is equal to the sum of the masses of the above two substances, and then grind all the substances in a ball mill to obtain a mixture B; (3) Drying the ground mixtures A and B to remove moisture; (4) calcining the dried mixtures A and B respectively, cooling them to room temperature after calcination, and grinding them into powder to obtain phosphorus-doped graphite carbon nitride and molybdenum-doped graphite carbon nitride respectively, and using them as two components in the heterojunction; (5) Put phosphorus-doped graphite carbon nitride, molybdenum-doped graphite carbon nitride and anhydrous ethanol into a stainless steel ball mill, wherein the mass ratio of phosphorus-doped graphite carbon nitride to molybdenum-doped graphite carbon nitride is 1:1, and the amount of anhydrous ethanol added is equal to the sum of the masses of the above two substances, and grind them in a ball mill; (6) After grinding, the product is dried, calcined, cooled to room temperature, and then ground into powder to obtain phosphorus-molybdenum co-doped graphite carbon nitride, which is used as a photocatalyst.

[0006] Furthermore, the nitrogen source compound is melamine or dicyandiamide.

[0007] Furthermore, in the steps (1) and (2), 50 to 200 g of bearing balls are added during grinding in a ball mill, and the rotation speed of the ball mill is controlled to be 200 to 350 r / min, and the grinding time is 0.5 to 2 hours.

[0008] Furthermore, in the step (3), the ground mixture is placed in a quartz crucible and dried in an oven at 50 to 80° C. for 1 to 3 hours to remove moisture.

[0009] Furthermore, in the step (4), the specific process of calcining the mixture is: heating the dried mixture to 500-550° C. in a muffle furnace at a heating rate of 5-10° C. / min, and calcining at this temperature for 3-5 hours.

[0010] Compared with the prior art, the advantages of the present invention are: (1) Phosphorus-molybdenum co-doped graphite carbon nitride with a Z-type heterojunction structure was prepared by wet ball milling, which effectively improved the electronic structure of graphite carbon nitride and significantly improved the separation efficiency of photogenerated electrons and holes.

[0011] (2) Through the co-doping of phosphorus and molybdenum, the oxidizability of holes in the valence band and the reducibility of electrons in the conduction band are enhanced, thereby improving the efficiency of the photocatalytic reaction. At the same time, the close contact between the semiconductor materials in the heterojunction effectively reduces the interface resistance and enhances the stability and photocatalytic activity of the photocatalyst.

[0012] (3) It can be used to degrade organic pollutants and antibiotic wastewater, especially rhodamine B and tetracycline (TC), with excellent degradation performance. The degradation rate of rhodamine B by PMo-C3N4 photocatalyst reaches 99% within 40 minutes, and the degradation rate of tetracycline reaches 80% within 60 minutes.

[0013] (4) The photocatalytic performance of PMo-C3N4 photocatalyst still maintains more than 90% of its catalytic activity after at least 5 cycles of use, and its reusability is good. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 It is the microstructure diagram of PMo-C3N4 of the present invention; Figure 2 Tauc plots of g-C3N4, P-C3N4, Mo-C3N4 and PMo-C3N4 of the present invention; Figure 3 VB-XPS spectra of g-C3N4, P-C3N4, Mo-C3N4 and PMo-C3N4 of the present invention; Figure 4 Schematic diagram of the potentials of the conduction band and valence band of two semiconductors in PMo-C3N4 of the present invention; Figure 5 FTIR spectra of Example 4 and Comparative Examples 1 to 3 of the present invention; Figure 6 PL spectra of Example 4 and Comparative Examples 1 to 3 of the present invention; Figure 7 The photoelectrochemical performance spectra of Example 4 and Comparative Examples 1 to 3 of the present invention are shown; Figure 8 It is a comparison chart of the photodegradation of organic pollutants rhodamine B (RhB) and tetracycline (TC) in Example 4 of the present invention and Comparative Examples 1 to 3; Fig. 9 Schematic diagram of the reuse performance of the PMo-C3N4 photocatalyst of the present invention. DETAILED DESCRIPTION

[0015] The present invention is further described in detail below with reference to the accompanying drawings.

[0016] Embodiment 1: A phosphorus-molybdenum co-doped graphite carbon nitride photocatalyst, whose molecular formula is PMo-C3N4, and is composed of 55% C, 40% N, 2.9% O, 2% P and 0.1% Mo elements in mass percentage, and the photocatalyst has a Z-type heterojunction structure.

[0017] Embodiment 2: A phosphorus-molybdenum co-doped graphite carbon nitride photocatalyst, whose molecular formula is PMo-C3N4, and is composed of 70% C, 25% N, 3.4% O, 1% P and 0.6% Mo elements in mass percentage, and the photocatalyst has a Z-type heterojunction structure.

[0018] Embodiment 3: A phosphorus-molybdenum co-doped graphite carbon nitride photocatalyst, whose molecular formula is PMo-C3N4, and is composed of 60% C, 34% N, 5% O, 0.7% P and 0.3% Mo elements in mass percentage, and the photocatalyst has a Z-type heterojunction structure.

[0019] In the above three embodiments, the constituent elements and relative contents of the photocatalyst are obtained through EDS mapping analysis.

[0020] Example 4: A method for preparing the above phosphorus-molybdenum co-doped graphite carbon nitride photocatalyst comprises the following specific steps: (1) 1 g of melamine, 0.1 g of sodium dihydrogen phosphate and 1.1 g of anhydrous ethanol were mixed in a stainless steel ball mill, and then all the substances were ground in a ball mill. During the grinding, 120 g of bearing balls were added, and the speed of the ball mill was controlled to 270 r / min. The grinding time was 1 hour to obtain a mixture A; (2) 1 g of melamine, 0.015 g of ammonium heptamolybdate tetrahydrate and 1.015 g of anhydrous ethanol were mixed in a stainless steel ball mill, and then all the substances were ground in a ball mill. During the grinding, 120 g of bearing balls were added, and the speed of the ball mill was controlled to 270 r / min. The grinding time was 1 hour to obtain a mixture B; (3) The ground mixtures A and B were placed in quartz crucibles respectively and dried in an oven at 80°C for 2 hours to remove moisture; (4) The dried mixtures A and B are heated to 550°C in a muffle furnace at a heating rate of 10°C / min and calcined at the temperature for 3 hours; after calcination, the mixtures are cooled to room temperature and ground into powder in an agate mortar to obtain phosphorus-doped graphite carbon nitride (P-C3N4) and molybdenum-doped graphite carbon nitride (Mo-C3N4), respectively, and used as two components in the heterojunction; (5) Mix 1 g of P-C3N4, 1 g of Mo-C3N4 and 2 g of anhydrous ethanol in a stainless steel ball mill, and grind them in a ball mill. During grinding, add 120 g of bearing balls, control the speed of the ball mill to 270 r / min, and grind for 1 hour. (6) After grinding, drying and calcining are performed, and the process parameters of the drying and calcining steps are the same as those of the above steps, and the mixture is cooled to room temperature and then ground into powder to obtain phosphorus-molybdenum co-doped graphite carbon nitride with the molecular formula PMo-C3N4, which is used as a photocatalyst.

[0021] In the above-mentioned fourth embodiment, melamine can be replaced by dicyandiamide, and sodium dihydrogen phosphate can be replaced by ammonium hexafluorophosphate or hexachlorocyclotriphosphazene.

[0022] Comparative Example 1: Preparation of photocatalyst graphite carbon nitride (g-C3N4), the specific process is: 2 g of melamine was heated to 550°C in a muffle furnace at a heating rate of 10°C / min and calcined at the temperature for 3 hours. After calcination, it was cooled to room temperature and ground into powder in an agate mortar to obtain graphite carbon nitride (g-C3N4).

[0023] Comparative Example 2: Preparation of photocatalyst phosphorus-doped graphite carbon nitride (P-C3N4), the specific process is: 2 grams of melamine, 0.1 grams of sodium dihydrogen phosphate and 2.1 grams of anhydrous ethanol were put into a stainless steel ball mill and mixed, and then all the substances were ground in a ball mill. During grinding, 120 grams of bearing balls were added, and the speed of the ball mill was controlled to be 270 r / min, and the grinding time was 1 hour; the ground mixture was loaded into a quartz crucible and dried in an oven at 80°C for 2 hours to remove moisture; the dried mixture was then heated to 550°C in a muffle furnace at a heating rate of 10°C / min, and calcined at this temperature for 3 hours; after calcination, it was cooled to room temperature and ground into powder in an agate mortar to obtain phosphorus-doped graphite carbon nitride (P-C3N4).

[0024] Comparative Example 3: The specific process of preparing the photocatalyst molybdenum-doped graphite carbon nitride (Mo-C3N4) is as follows: 2 g of melamine, 0.015 g of ammonium heptamolybdate tetrahydrate and 2.015 g of anhydrous ethanol were mixed in a stainless steel ball mill. During grinding, 120 g of bearing balls were added, and the speed of the ball mill was controlled to be 270 r / min, and the grinding time was 1 hour. The ground mixture was placed in a quartz crucible and dried in an oven at 80°C for 2 hours to remove moisture. The dried mixture was then heated to 550°C in a muffle furnace at a heating rate of 10°C / min and calcined at this temperature for 3 hours. After calcination, it was cooled to room temperature and ground into powder in an agate mortar to obtain molybdenum-doped graphite carbon nitride (Mo-C3N4).

[0025] The microstructure of phosphorus-molybdenum co-doped graphite carbon nitride (PMo-C3N4) prepared by the present invention is analyzed and verified.

[0026] (I) The microstructure of PMo-C3N4 was studied by transmission electron microscopy (TEM), such as Figure 1 As shown in a, the sample exhibits an ultra-thin nanosheet structure with obvious porous characteristics. TEM results confirm the composite sheet and porous structure of PMo-C3N4, which helps to enhance the catalytic activity of PMo-C3N4. Figure 1 It can be observed in b that PMo-C3N4 has a tightly bound heterojunction interface, which indicates that PMo-C3N4 forms a stable heterojunction structure.

[0027] (II) Verify the heterojunction structure of phosphorus-molybdenum co-doped graphite carbon nitride (PMo-C3N4), specifically: By plotting the Tauc plot of (αhν)² versus photon energy (hν) and finding the intercept of the tangent line, the band gap energy of PMo-C3N4 can be estimated, as Figure 2 As shown, according to the Kubelka-Munk model: ( αhν ) n = A( hν−E g ), in, α is the absorption coefficient, h is Planck's constant (4.1356676969×10-15), ν is the frequency of light, A is a constant, Eg is the band gap energy, n is a constant used to indicate the band gap type of the material, n=1 / 2 for indirect band gap semiconductors, and n=2 for direct band gap semiconductors. The band gap energies of g-C3N4, P-C3N4, Mo-C3N4 and PMo-C3N4 are 2.80eV, 2.70eV, 2.76eV and 2.65eV respectively. The narrowing of the band gap is conducive to enhancing the absorption capacity of visible light, thereby improving the photoactivity.

[0028] Valence band potential E of g-C3N4, P-C3N4, Mo-C3N4, and PMo-C3N4 VB From the VB-XPS spectrum, such as Figure 3 As shown. Due to the contact potential difference between the sample and the XPS analyzer, the valence band potential of the sample at the standard hydrogen electrode can be calculated according to the relationship: E VB = E VB- XPS + φ -4.44eV Calculate, where E VB-XPS is the value measured by the VB-XPS graph, φ is the work function of the XPS analyzer (4.2eV), therefore, the valence band potentials of g-C3N4, P-C3N4, Mo-C3N4, and PMo-C3N4 on the standard hydrogen electrode are 2.23eV, 2.12eV, 1.96eV, and 1.77eV, respectively. The conduction band potential E of the sample is deduced according to the relationship CB : E CB =E VB -E g , E of g-C3N4, P-C3N4, Mo-C3N4, PMo-C3N4 CBThey are -0.57eV, -0.58eV, -0.80eV and -0.88eV respectively. Figure 4 This is a schematic diagram of the potentials of the conduction band and valence band of the two semiconductors in PMo-C3N4. From the relative arrangement of the energy bands, it can be determined that the heterojunction type in PMo-C3N4 is Z-type.

[0029] The photocatalysts prepared in the above-mentioned Example 4 and Comparative Examples 1 to 3 were characterized and analyzed.

[0030] (I) FTIR spectra of g-C3N4, P-C3N4, Mo-C3N4 and PMo-C3N4 were analyzed respectively. Figure 5 As shown, the 1200-1700 cm -1 The peak intensity of the region is lower than that of other photocatalysts, which indicates that the construction of the heterojunction promotes the realignment of the conduction band and the valence band and promotes the close binding of P and Mo elements with g-C3N4.

[0031] (ii) PL spectra of g-C3N4, P-C3N4, Mo-C3N4, and PMo-C3N4 were analyzed respectively. Figure 6 As shown in the PL spectrum, the PL peak intensity of PMo-C3N4 is significantly reduced, which indicates that the intermediate energy state caused by doping traps electrons and holes in the tri-s-triazine ring and promotes their separation from each other. This means that it has higher photocatalytic activity because the lower electron-hole recombination rate means that more electrons can participate in the catalytic reaction.

[0032] (III) The photoelectrochemical performance of g-C3N4, P-C3N4, Mo-C3N4 and PMo-C3N4 were analyzed respectively. Figure 7 As shown in a, the photocurrent response of PMo-C3N4 is much higher than that of the other samples. This is attributed to the existence of the Z-type heterojunction, which allows photogenerated electrons and holes to migrate along independent paths, reducing their recombination probability and thus enhancing the generation and separation of carriers. In the EIS Nyquist plot, the radius of curvature of the arc corresponds to the transfer resistance of the carriers. The PN bond and the Mo-N bond form a good chemical bond at the heterojunction interface, which significantly reduces the interface resistance of PMo-C3N4, as shown in Figure 1. Figure 7 As shown in b, the effective transmission of photogenerated electrons is accelerated, effectively improving its catalytic activity.

[0033] (IV) Photocatalytic performance tests were conducted on g-C3N4, P-C3N4, Mo-C3N4 and PMo-C3N4 respectively: (1) Test of organic wastewater degradation performance: 20 mg of g-C3N4, P-C3N4, Mo-C3N4, and PMo-C3N4 were added to 100 mL of 20 mg / L Rhodamine B (RhB) solution, and the suspension was magnetically stirred in a dark environment for 30 minutes to ensure that a uniform adsorption-desorption equilibrium was achieved. Then a 300W xenon lamp (CEL-HXF300) was used for photocatalytic reaction. 2 mL of solution sample was taken out every 10 minutes, and the photocatalyst was separated by high-speed centrifugation. The absorbance of the solution was immediately measured at 554 nm using a UV-visible spectrophotometer (Lambda 650) to analyze the change in solution concentration, such as Figure 8 As shown in (a), PMo-C3N4 almost completely degraded RhB at 40 min.

[0034] (2) Antibiotic wastewater degradation performance test: 40 mg of g-C3N4, P-C3N4, Mo-C3N4, and PMo-C3N4 were dispersed in 100 mL of 25 mg / L tetracycline (TC) solution. The experimental and sampling methods were the same as those of the above organic wastewater degradation test. The absorbance of the solution was measured at 357 nm using a UV-visible spectrophotometer to analyze the changes in solution concentration, such as Figure 8 As shown in (b), the degradation rate of TC by PMo-C3N4 reached 80% within 60 min, which was significantly improved compared with the control group.

[0035] Among them, P-C3N4 and Mo-C3N4 are two components of the PMo-C3N4 photocatalyst. It can be seen that compared with the catalyst doped with a single element, the photocatalytic performance of the Z-type heterojunction photocatalyst PMo-C3N4 constructed by co-doping phosphorus and molybdenum is significantly improved. This is attributed to the synergistic effect of phosphorus and molybdenum to effectively adjust the electronic energy levels of the valence band and conduction band of the material, and construct a Z-type heterojunction structure with good energy band matching, thereby enhancing the oxidizability of holes in the valence band and the reducibility of electrons in the conduction band. At the same time, the two semiconductor materials in the heterojunction are in close contact, which effectively reduces the interface resistance and enhances the stability and photocatalytic activity of the catalyst.

[0036] (V) In order to evaluate the industrial application potential of PMo-C3N4, the PMo-C3N4 photocatalyst was recovered at the end of each degradation experiment and continued to be used in the next cycle. Fig. 9As shown in the figure, after 5 consecutive cycles, the degradation efficiency of PMo-C3N4 did not change much, and 90% of the catalytic activity was retained. This is mainly attributed to the stability of the Z-type heterojunction structure, which ensures efficient photogenerated carrier separation and photocatalytic activity during multiple uses, indicating that the prepared PMo-C3N4 photocatalyst has good reusability. In order to further study the morphology, structure and chemical stability of the photocatalyst, SEM and FTIR analysis were performed on the samples before and after the photocatalytic reaction. The FTIR spectra before and after the reaction were almost the same, and no obvious changes were observed in the microscopic morphology, further proving that the Z-type heterojunction of PMo-C3N4 has excellent stability. These results show that PMo-C3N4 not only has efficient photocatalytic performance, but also has good stability and recyclability, and has broad application prospects.

[0037] The protection scope of the present invention includes but is not limited to the above embodiments, and its protection scope is subject to the claims. Any replacement, deformation, and improvement of the technology that can be easily thought of by technicians in this field shall fall within the protection scope of the present invention.

Claims

1. A phosphorus-molybdenum co-doped graphite carbon nitride photocatalyst, characterized in that The molecular formula is PMo-C3N4, and it is composed of 52% to 70% C, 25% to 40% N, 1.5% to 6% O, 0.2% to 2% P and 0.05% to 0.6% Mo element by mass percentage, and the photocatalyst has a Z-type heterojunction structure.

2. The method for preparing a phosphorus-molybdenum co-doped graphite carbon nitride photocatalyst according to claim 1, characterized in that The specific steps include: (1) Sodium dihydrogen phosphate, ammonium hexafluorophosphate or hexachlorocyclotriphosphazene, a nitrogen source compound and anhydrous ethanol are placed in a stainless steel ball mill and mixed, wherein the mass ratio of sodium dihydrogen phosphate or ammonium hexafluorophosphate or hexachlorocyclotriphosphazene to the nitrogen source compound is 0.05-0.25:0.5-5, and the amount of anhydrous ethanol added is equal to the sum of the masses of the above two substances, and then all the substances are ground in a ball mill to obtain a mixture A; (2) Place a nitrogen source compound, ammonium heptamolybdate tetrahydrate and anhydrous ethanol in a stainless steel ball mill and mix them, wherein the mass ratio of the nitrogen source compound to ammonium heptamolybdate tetrahydrate is 0.5-5:0.005-0.1, and the amount of anhydrous ethanol added is equal to the sum of the masses of the above two substances, and then grind all the substances in a ball mill to obtain a mixture B; (3) Drying the ground mixtures A and B to remove moisture; (4) calcining the dried mixtures A and B respectively, cooling them to room temperature after calcination, and grinding them into powder to obtain phosphorus-doped graphite carbon nitride and molybdenum-doped graphite carbon nitride respectively, and using them as two components in the heterojunction; (5) Put phosphorus-doped graphite carbon nitride, molybdenum-doped graphite carbon nitride and anhydrous ethanol into a stainless steel ball mill, wherein the mass ratio of phosphorus-doped graphite carbon nitride to molybdenum-doped graphite carbon nitride is 1:1, and the amount of anhydrous ethanol added is equal to the sum of the masses of the above two substances, and grind them in a ball mill; (6) After grinding, it is dried, calcined, cooled to room temperature, and then ground into powder to obtain phosphorus-molybdenum co-doped graphite carbon nitride, which is used as a photocatalyst.

3. The method for preparing a phosphorus-molybdenum co-doped graphite carbon nitride photocatalyst according to claim 2, characterized in that: The nitrogen source compound is melamine or dicyandiamide.

4. The method for preparing a phosphorus-molybdenum co-doped graphite carbon nitride photocatalyst according to claim 2, characterized in that: In the steps (1) and (2), when grinding in the ball mill, 50 to 200 g of bearing balls are added, and the rotation speed of the ball mill is controlled to be 200 to 350 r / min, and the grinding time is 0.5 to 2 hours.

5. The method for preparing a phosphorus-molybdenum co-doped graphite carbon nitride photocatalyst according to claim 2, characterized in that: In the step (3), the ground mixture is placed in a quartz crucible and dried in an oven at 50 to 80° C. for 1 to 3 hours to remove moisture.

6. The method for preparing a phosphorus-molybdenum co-doped graphite carbon nitride photocatalyst according to claim 2, characterized in that: In the step (4), the specific process of calcining the mixture is: heating the dried mixture to 500-550° C. in a muffle furnace at a heating rate of 5-10° C. / min, and calcining at this temperature for 3-5 hours.